PENGAWASAN UNIT APRON MOVEMNT CONTROL (AMC) TERHADAP DISIPLIN PENGGUNA JASA DI BANDAR UDARA KOMODO LABUAN BAJO - Ririn Agus Triana; Faiz Albanna, S.Kom., M.Kom (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Apron Movement Control (AMC) is an airport personnel who has a license and rating to carry out supervision of order, safety of traffic movements on the apron, ensure the cleanliness of the apron area and determine aircraft parking. One of the aims of the supervision carried out by Apron Movement Control (AMC) is to create discipline for service users in flight activities. The purpose of this study was to find out how the Apron Movement Control unit supervises service user discipline and how the Apron Movement Control unit disciplines service users at Komodo Airport Labuan Bajo. This research is a qualitative research using primary data and secondary data. Data collection techniques used are observation, interviews and documentation. The observation is to conduct a review or direct observation on the AMC unit. Interviews in this study were 2 AMC personnel. The documentation is taking data during observations and interviews, as well as taking pictures during field activities. The results of this study can be concluded that the supervision of the AMC unit on the discipline of service users is to supervise all operational activities on the apron such as supervision of the speed of GSE vehicles and also officers' vehicles, supervision of the mobility of people or passengers, supervision of equipment that must be used by officers such as safety vests, supervision of engine running up, supervision during refuelling, and also supervision of the cleanliness of the apron area. The way the AMC unit disciplines service users on the air side (apron) is to supervise all mobility of people/passengers, then for Ground Handling officers if they violate the rules, they must take action from AMC. The action taken is a direct warning to the person concerned and if the warning is given to the same person three times, then the airport is revoked or detained, so that the person concerned is not allowed or prohibited to work in the apron area or in the air side area